Letter to Jane Tolmach; from Louis R. Nash - Louis R. Nash:::::: (1965)
Louis R. Nash (Superintendent Medical Director) sent a letter to Jane Tolmach on January 5, 1965. The purpose of this letter is to inform Tolmach about a change of date for their future Board meeting which was originally scheduled on January 28, 1965 but has not been pushed to February 25. The reason for this is to allow Board members to attend Mr.Baptista's location Brown Derby.